TINJAUAN LITERATUR FINANCIAL LITERACY DAN PENGARUHNYA PADA BIAS KEUANGAN - Bayu Laksma Pradana; andreas kiky (Jurnal Bina Manajemen, 2022)
Financial Literacy has been known as a factor influencing decision making. Financial literacy is knowledge, skill, and attitude of a person regarding finance. Researchers use subjective and objective financial literacy to measure how literate a person is. One of behavior finance observation is to study how mind can be affected by bias. There are many biases that people should be aware of. Such bias can make people suffer from financial loss. Studies have shown there is a relation between financial literacy and bias. The more literate, the better he can avoid bias. This study explains the theory of financial literacy and financial bias. Previous works have been thoroughly selected to provide evidence.